Sustainable Corporate Strategies: The Influence of Green Human Resource Management (GHRM) on Environmental Performance (EP) with OCBE as a Mediator in the Manufacturing Industry - Hutabarat, Srey Mariati; Sulistyaningsih, Endang (Yayasan Riset dan Pengembangan Intelektual, 2025)
This study aims to analyze the effect of Green Human Resource Management (GHRM) on Environmental Performance (EP) with the mediation role of Organizational Citizenship Behavior for the Environment (OCBE). The study was conducted at PT. Merah Putih, a manufacturing company in Indonesia, involving 241 respondents. The results showed that GHRM had a significant effect on EP, both directly and through increasing OCBE as a partial mediator. OCBE contributed to strengthening the impact of GHRM policies on EP, where employee pro-environmental behavior, such as energy saving and waste management, supported the company's operational efficiency. These findings emphasize the importance of a holistic approach in implementing GHRM to encourage employee pro-environmental behavior and improve the company's environmental performance. The study provides recommendations for companies to strengthen environmental training programs, increase employee involvement in sustainability initiatives, and evaluate the effectiveness of GHRM policies periodically.